Иван IV Грозный - Володихин Дмитрий Михайлович (Государство и Власть, 2010)
Экземпляры: СЭ (20110516) / Инвентарный номер: 1083655 / Цена: / Сис.шифр: 63.3(2)4 / Авт.знак: В 68 / ГРНТИ: 03 / ББК: 63.3(2)43